Study of The In Vivo Anti-Inflammatory, Antipyretic and Analgesic Effect of The Ethanol Extract Indian Nettle Plant (Acalypha indica Linn) - Khairani, Sondang; Ros Sumarny; Yurista Elystra (Faculty of Pharmacy Universitas Pancasila, 2024)
The body can experience fever and pain, when inflammation occurs. Indian nettle plant (Acalypha Indica Linn.) are known to contain flavonoid compounds which are thought to have anti-inflammatory, antipyretic, and analgesic effect. This study aims to test the anti-inflammatory, antipyretic, and analgesic effect of the ethanol extract of 70% Indian Nettle plant. Method each test used 5 groups, negative control all given Na CMC 0,5%. Antiinflammatory use rats with Winter method, aspirin 40,43mg/200gBB, the test group dose 70mg/200gBW (I), 140mg/200gBW (II), 280mg/200gBW (III), antipyretics use rats with Brewer's yeast method, aspirin 21,45mg/200gBW, the test group dose 70mg/200gBW (I), 140mg/200gBW (II), 280mg/200gBW (III). Analgesic use mice with the Siegmund method, aspirin 3,10mg/20gBB, the test group dose of 10mg/20gBB (I); 20mg/20gBB (II); 40mg/20g BW (III). Results Kruskall Wallis test, the anti-inflammatory effect significant difference to negative control, p value <0,05. Percentage of inhibition positive control edema and test dosage I, II, and III obtained 34,44%; 18,88%; 21,37%, and 29,61%. The Mann Whitney test, the antipretic and analgesic effects significant difference to the negative control, p value <0,05. The decreased percentage of fever in positive control and dosage I, II, and III test preparations was 3,74%; 2,60%; 2,55%; 3,01%. Inhibition percentage of stretching positive control and test dosage I, II, and III obtained 41,05%; 24,46%; 27,78%; and 33,31%. Conclussion: Wriggling inhibition (analgesic) had the highest presentation dose III 33,31% compare to anti-inflammatory and antipyretic activities, lower than aspirin as positive control 41,05% (p<0,05).